219k views
2 votes
Please answer correctly !!!!!!! Will mark Brianliest !!!!!!!!!!!

Please answer correctly !!!!!!! Will mark Brianliest !!!!!!!!!!!-example-1
User Lynden
by
4.4k points

1 Answer

5 votes

Answer:


x=-2\\x=2

(You only need to give one solution)

Explanation:

We have the following equation


(x^2+1)^2-5x^2-5=0

First, we need to foil out the parenthesis


x^4+2x^2+1-5x^2-5=0

Now we can combine the like terms


x^4-3x^2-4=0

Now, we need to factor this equation.

To factor this, we need to find a set of numbers that add together to get -3 and multiply to give us -4.

The pair of numbers that would do this would be 1 and -4.

This means that our factored form would be


(x^2-4)(x^2+1)=0

As the first binomial is a difference of squares, it can be factored futher into


(x^2+1)(x+2)(x-2)=0

Now, we can get our solutions.

The first binomial will produce two complex (Not real) solutions.


x+2=0\\\\x=-2


x-2=0\\\\x=2

So our solutions to this equation are


x=-2\\x=2

User Lovalery
by
5.6k points